Relationship between Depression and Adherence to Treatment among Patients with Type II Diabetes Mellitus - Alinka C. Rojas; Penate L. Cova (Academic Journal of Clinicians, 2025)
Diabetes mellitus (DM) is characterized by the manifestation of hyperglycemia attributable to alterations in insulin secretion, insulin action, or both. Over a prolonged period, it affects a variety of organs, including the eyes, kidneys, nerves, heart, and blood vessels. The primary symptoms of diabetes mellitus include polyuria, polydipsia, polyphagia, blurred vision, and weight loss. However, within the diagnosis of diabetes mellitus, subclassifications can be identified. These depend on multiple factors during the diagnostic process, and within the corresponding categories or classifications, the following categories can be identified. Treatment adherence is defined as the level to which patients comply with the treatment and guidelines prescribed by the physician. It has been clearly demonstrated that treatment adherence has a positive and significant impact on the results of cure or treatment of chronic diseases. According to the World Health Organization, treatment adherence in chronic diseases does not exceed 50%, and such levels could be lower in developing nations. However, to date, a clear method has not been established to prevent non-adherence, since there is no pattern to identify or predict future treatment abandonment. Depression is a chronic and widespread medical condition that can affect cognitive processes, mood, and physical health. It is characterized by an unfavorable mood, lack of energy, sadness, insomnia, and an inability to appreciate existence. However, clinical research to date has shown that patients with depression do not obtain a satisfactory therapeutic outcome. Depression contributes to more years of disability annually than other pathologies, impacting more than 350 million individuals annually.